Principles of Household Debt Restructuring - Laryea, Thomas (IMF Staff Position Notes; Staff Position Note, 2009)
This paper examines the estimated compliance with the macroeconomic convergence targets for 2008, based on estimates contained in the IMF's Regional Economic Outlook: Sub-Saharan Africa (the REO). SADC's regional economic integration agenda includes a macroeconomic convergence program, intended to achieve and maintain macroeconomic stability in the region, thereby contributing to faster economic growth and laying the basis for eventual monetary union. Targets for key macroeconomic variables have been set out for 2008, 2012, and 2018. Most SADC member states have recorded solid macroeconomic performance in recent years, in general coming close to, and in many cases surpassing, the convergence targets specified for 2008. A notable exception in this regard is Zimbabwe, which was in the grip of hyperinflation. The macroeconomic targets for 2012 are ambitious and, in some cases, warrant further evaluation, given that achieving the targets may be neither necessary nor sufficient to achieve good macroeconomic results.